An Empirical Study on The Relationship between Career Administration and Career Success: An Islamic Perspective - Mohd Nowalid, Wan Aishah Wan; Raja Hisham, Raja Rizal Iskandar; Ahmad Sabri, Nurul Syazwani; Abd Halim, Siti Noorjannah (UUM Press, 2024)
Career administration is essential for achieving career goals, relying on efficient management, particularly through job autonomy and transformational leadership. Research indicates that promoting job autonomy and implementing transformational leadership positively impacts employees’ career success, including promotions and satisfaction. However, practical issues such as inconsistent management practices and lack of support for job autonomy have hindered career success in many organizations. This study addresses these industry challenges by examining how job autonomy and transformational leadership influence career success within Malaysian government agencies from an Islamic perspective. By recognizing the difficulties employees face in maintaining efficiency and job performance, this research aims to understand how organizations can utilize career administration strategies to overcome these obstacles and enhance employee career success. A survey of 215 employees revealed two significant findings: firstly, career administration is positively and substantially correlated with promotions, and secondly, career administration positively linked to career satisfaction within the organization. These results highlighted the importance of career administration as a factor affecting career success. The study contributes to our understanding of how organizations can foster a positive work environment able to lead to a better organizational outcome